2016
DOI: 10.1002/2016gl068207
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical processing of diesel fuel emissions as a large secondary source of isocyanic acid (HNCO)

Abstract: Isocyanic acid (HNCO) is a well‐known air pollutant that affects human health. Biomass burning, smoking, and combustion engines are known HNCO sources, but recent studies suggest that secondary production in the atmosphere may also occur. We directly observed photochemical production of HNCO from the oxidative aging of diesel exhaust during the Diesel Exhaust Fuel and Control experiments at Colorado State University using acetate ionization time‐of‐flight mass spectrometry. Emission ratios of HNCO were enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 50 publications
(98 reference statements)
8
82
0
Order By: Relevance
“…HNCO mixing ratios were possibly influenced by additional sources, including traffic, ONG wells, and industrial activity. Traffic exhaust is a primary emission source of HNCO (Brady et al, 2014;Link et al, 2016), but the lack of a morning rush-hour peak or correlation with CO suggests that it was not a strong primary source of HNCO at the site (Fig. 2).…”
Section: Isocyanic Acidmentioning
confidence: 99%
See 3 more Smart Citations
“…HNCO mixing ratios were possibly influenced by additional sources, including traffic, ONG wells, and industrial activity. Traffic exhaust is a primary emission source of HNCO (Brady et al, 2014;Link et al, 2016), but the lack of a morning rush-hour peak or correlation with CO suggests that it was not a strong primary source of HNCO at the site (Fig. 2).…”
Section: Isocyanic Acidmentioning
confidence: 99%
“…2). Link et al (2016) found that diesel exhaust was a precursor for photochemical HNCO production, but Jathar et al (2017) suggested that the kinetics do not substantially outcompete dilution, and that urban HNCO is not strongly enhanced by diesel exhaust photochemistry.…”
Section: Isocyanic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…The former study reported evidence for the incorporation of nitrogen into SOA. OFRs have also been increasingly employed to process emissions of vehicles, biomass burning, and other combustion sources (Table 1) in which NO can often be hundreds of ppm Martinsson et al, 2015;Karjalainen et al, 2016;Link et al, 2016;Schill et al, 2016;Alanen et al, 2017;Simonen et al, 2017). It can be expected that such a high NO input together with very high VOC concentrations would cause a substantial deviation from the good OFR operation conditions identified in Peng et al (2016).…”
Section: Introductionmentioning
confidence: 99%